Reed carbon fiber negative electrode material for sodium ion battery as well as preparation method and application of reed carbon fiber negative electrode material

By combining reed charcoal fibers with UIO66-4F, the negative electrode materials for sodium ion batteries are prepared, and the problem of low biomass material utilization rate is solved, and efficient and stable sodium ion storage and electrochemical performance improvement has been achieved.

CN119381419AActive Publication Date: 2025-01-28CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411294008.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-28
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The prior art has low utilization rate of biomass materials, especially in sodium ion batteries, which lead to waste of resources and environmental pollution, and lacks technical solutions that can efficiently and stably apply reeds as negative electrode materials.

Method used

The reed charcoal fiber is used as the vector of the negative electrode material of the sodium ion battery, and the surface covering and high temperature carbonization are combined with the combination of the solvent thermal reaction with the UIO66-4F to prepare the negative electrode material with high-efficiency and stable sodium ion storage active sites.

Benefits of technology

Improve the ratio and stability of the negative electrode material of sodium ion batteries, enhance the area of ​​electrochemical activity, improve the efficiency of sodium ion transmission, extend the battery cycle life, and realize the high value -added utilization of biomass materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381419A_ABST
    Figure CN119381419A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage materials, and provides a reed carbon fiber negative electrode material for a sodium ion battery as well as a preparation method and application of the reed carbon fiber negative electrode material. The preparation method comprises the following steps: (1) pretreating the reeds; (2) adding the reed obtained in the step (1) into a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N, N-dimethylformamide and acetic acid, carrying out solvothermal reaction, cleaning and drying to obtain uio66-4f; and (3) performing high-temperature carbonization on the reed material with the surface coated with uio66-4f obtained in the step (2) in a protective atmosphere to obtain the reed carbon fiber negative electrode material for the sodium-ion battery. The reed carbon fiber with a large number of mesopores is adopted as a sodium ion battery negative electrode material carrier and is combined with uio66-4f with fluorine atoms, a large number of efficient and stable sodium ion storage active sites can be provided, and the sodium ion transmission efficiency is improved; meanwhile, more active sites can be easily exposed, the electrochemical active area of the negative electrode material is increased, and rapid permeation and diffusion of electrolyte are facilitated, so that the specific capacity and stability of the battery negative electrode material are easily improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy storage materials, and specifically relates to a reed carbon fiber negative electrode material for a sodium ion battery and a preparation method and application thereof. Background Art

[0002] With the improvement of social productivity, global energy demand is expected to increase rapidly in the next few decades. At present, the energy consumed by social production is mainly natural fossil energy (such as oil, coal, and natural gas). While natural energy is used for energy supply and exploitation, it also brings about a series of problems such as ecological environment deterioration and greenhouse effect, which greatly hinders the sustainable development of ecology. Under this prospect, the development of clean and renewable energy is very important. Human beings have been accelerating the development of renewable energy, but due to seasonal and geographical factors, the distribution of renewable energy is uneven and intermittent, and the proportion of renewable energy that can be directly consumed is very small. Therefore, converting these renewable energy sources into electrical energy for efficient storage will be conducive to the virtuous cycle of energy development.

[0003] At present, lithium-ion batteries are the most widely used energy storage battery system. As the production cost of lithium-ion batteries continues to rise, the demand for resource-rich and low-cost alternatives has emerged, and sodium-ion batteries have gradually become a potential alternative to lithium-ion batteries. However, the large radius of sodium ions and slow diffusion kinetics make it impossible to directly use graphite anode materials that have been shining in lithium-ion batteries in sodium-ion batteries. Finding sodium-ion battery anode materials with satisfactory first coulombic efficiency, high rate performance and long life has become a new challenge in the development of sodium-ion batteries.

[0004] Among all the current materials, hard carbon is the best choice for sodium ion negative electrode materials because it has a large interlayer distance, abundant micropores / mesopores, and low redox potential, and can accommodate sodium ions with a considerable capacity. Biomass-based hard carbon uses woody plants, grasses, vines, and their processing residues and waste as raw materials. It is processed and manufactured through high-tech means such as physics, chemistry, and biology to produce hard carbon materials with excellent performance and high added value. At the same time, biomass-based materials are considered to be one of the most abundant renewable resources on the earth and have extremely high utilization value. Common biomass materials include reeds, wood, bamboo, starch, bark, cellulose, lignin, hemicellulose, protein, chitin, etc. Among them, the cellulose content in reed is 55.82%, including 79.97% cellulose, 20.03% hemicellulose, 1.52mm fiber length, and 23.52% lignin. At the same time, there are many active groups such as hydroxyl and carboxyl on its surface, and the surface active sites are rich. These active groups can provide reaction carriers for the recombination of reed and exogenous heterogeneous functional components. It has rich mesoporous structure, which provides a lot of storage space for sodium ions, making it an ideal raw material for negative electrode materials of sodium ion batteries. The efficient and comprehensive utilization of reed resources not only has significant ecological significance in the context of the severe natural environment of the century, but also has far-reaching economic and social benefits. However, the current level of processing and utilization of biomass materials in my country is not high. Reeds are widely used as a green material mainly in the textile, construction and other industries. The reed residues generated during the utilization process are generally abandoned in lakes or used as ordinary fuel. There are few reports on their application as negative electrode materials for sodium ion batteries, which not only causes serious waste of resources, but also causes serious pollution to the environment. Some existing methods of using reeds as negative electrode materials for sodium ion batteries also cause serious volume expansion (up to 300%) in the process of sodiumization and de-sodiumization of Si contained in reeds, which will lead to a decrease in the mechanical stability of the negative electrode material, and it is easy to cause structural damage and pulverization, which will eventually lead to a decrease in the cycle life of the electrode.

[0005] Therefore, there is currently a lack of a technical solution that can efficiently and stably use reeds as biomass materials in sodium batteries. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the utilization rate of biomass materials in the prior art is low, the deficiencies and defects mentioned in the above background technology are overcome, and a reed carbon fiber negative electrode material for sodium ion battery and a preparation method and application thereof are provided.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0008] A method for preparing a reed carbon fiber negative electrode material for a sodium ion battery, characterized in that it comprises the following steps:

[0009] (1) Pre-treating reeds;

[0010] (2) adding the reed obtained in step (1) to a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N,N-dimethylformamide and acetic acid, performing a solvent thermal reaction, washing and drying to obtain uio66-4f;

[0011] (3) The reed material with surface coated with uio66-4f obtained in step (2) is carbonized at high temperature under a protective atmosphere to obtain a preparation method for a reed carbon fiber negative electrode material for a sodium ion battery.

[0012] Reeds are added to a solution containing tetrafluoroterephthalic acid and zinc nitrate, and UIO66-4F is synthesized and coordinated in a conventional manner to form a metal-organic framework complex. In addition, the zinc ions in UIO66-4F evaporate during the high-temperature carbonization process, providing sites for the storage of sodium ions while maintaining the original framework structure. Other transition metal salts are difficult to volatilize during the high-temperature carbonization process. N, N-dimethylformamide is a solvent with high solubility for both tetrafluoroterephthalic acid and zinc nitrate, and acetic acid can adjust the pH value of the solution and promote the reaction.

[0013] Preferably, the pretreatment in step (1) comprises: soaking the reeds in a sodium hydroxide solution, stirring for 2 to 8 hours, washing with deionized water and drying.

[0014] Pretreatment is to remove silicon from reeds. The chemical reaction of silicon removal is: SiO2+2NaOH→Na2SiO3+H2O. In this reaction, solid silicon dioxide reacts with sodium hydroxide solution to generate soluble sodium silicate (Na2SiO3) and water.

[0015] More preferably, the concentration of the sodium hydroxide solution is 1 wt% to 5 wt%.

[0016] Preferably, the reaction temperature of the solvent thermal reaction in step (2) is 120-220° C., and the reaction time is 8 to 48 hours.

[0017] Preferably, in step (2), the mass ratio of tetrafluoroterephthalic acid to zinc nitrate is 1:2 to 2:3, and the volume ratio of N,N-dimethylformamide to acetic acid is 5:7.

[0018] More preferably, in laboratory operation, the amount of reed added in step (2) does not exceed 20 g.

[0019] Preferably, the cleaning in step (2) uses ethanol, and the drying temperature is 40-80° C. and the drying time is 6-18 hours.

[0020] Preferably, the protective atmosphere in step (3) is a nitrogen or argon atmosphere, and the high-temperature carbonization adopts a two-stage sintering, the first stage sintering is heated to 350-600°C at a heating rate of 2-5°C / min, and kept warm for 1-2h; the second stage sintering is heated to 800-1000°C at a heating rate of 2-5°C / min, and kept warm for 1-2h. Here, the two-stage sintering method is used for high-temperature carbonization, because zinc nitrate will volatilize during the carbonization process, and heating too quickly will cause the material structure to collapse. The two-stage sintering can stabilize the structural morphology of the material while ensuring the completion of carbonization.

[0021] Preferably, the reed is fibrous, has a fiber diameter of 8-10 μm, and is produced in the Dongting Lake area.

[0022] Under the same technical concept, the present invention also provides a reed carbon fiber negative electrode material for a sodium ion battery. The negative electrode material is prepared by the preparation method of the reed carbon fiber negative electrode material for a sodium ion battery. The negative electrode material uses reed carbon fiber as a carrier, and the surface of the reed carbon fiber is coated with UIO66-4F.

[0023] Under the same technical concept, the present invention also provides a reed carbon fiber negative electrode material for a sodium ion battery, and the reed carbon fiber negative electrode material is used in a sodium ion battery.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention uses reed, a biomass material with a wide range of sources, green and environmentally friendly, and a large number of mesopores, as the raw material for preparing the negative electrode of the sodium ion battery. The preparation process is simple and easy, and can effectively solve the problem of high value-added utilization of biomass materials;

[0026] (2) The present invention uses reed carbon fiber with a large number of mesopores as a carrier of the negative electrode material of the sodium ion battery, and combines it with UIO66-4F with fluorine atoms to provide a large number of efficient and stable sodium ion storage active sites, thereby improving the sodium ion transmission efficiency; at the same time, it is beneficial to expose more active sites, increase the electrochemical active area of ​​the negative electrode material, and facilitate the rapid penetration and diffusion of the electrolyte, thereby facilitating the improvement of the specific capacity and stability of the battery negative electrode material;

[0027] (3) The microscopic morphology of the reed carbon fiber negative electrode material for sodium ion batteries of the present invention is fibrous, with a diameter of 8 to 10 μm. Since the reed carbon fiber negative electrode material for sodium ion batteries has unique anisotropy, fast axial electron transport and radial ion diffusion characteristics, when used as a click active material, the sodium ion migration path will be greatly shortened, and the sodium ions can quickly shuttle through it, thereby improving the rate performance of the sodium ion battery, having a large specific capacity and good cycle stability;

[0028] (4) The preparation method of the present invention first pre-treats the reed carbon fiber to remove the silicon element therein, thereby preventing the silicon from experiencing severe volume expansion during the sodiumization and de-sodiumization processes; the doping modification of the organic ligand and the metal ion is completed in a one-step method, and the introduction process of the heteroatom is simple and easy to repeat, which reduces the complexity of the process, reduces time and cost, and has significant economic advantages in large-scale production. At the same time, under high temperature and high pressure hydrothermal conditions, the reactant molecules have higher energy and can react quickly to generate the target product. This makes the reaction efficiency higher, shortens the synthesis time, and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 It is a schematic diagram of the preparation method of the present invention;

[0031] Figure 2 The scanning electron microscope (SEM) images of the reed carbon fiber negative electrode material for sodium ion battery prepared in Examples 1 to 4 of the present invention; wherein ae is Example 1, bf is Example 2, cg is Example 3, and dh is Example 4;

[0032] Figure 3 This is a first charge and discharge curve diagram of the reed carbon fiber negative electrode material for sodium ion battery in Example 1 of the present invention;

[0033] Figure 4 This is a first charge and discharge curve diagram of the reed carbon fiber negative electrode material for sodium ion battery in Example 2 of the present invention;

[0034] Figure 5 This is the first charge and discharge curve of the reed carbon fiber negative electrode material for sodium ion battery in Example 3 of the present invention;

[0035] Figure 6 This is a first charge and discharge curve diagram of the reed carbon fiber negative electrode material for sodium ion battery in Example 4 of the present invention;

[0036] Figure 7 This is the first charge and discharge curve of the reed fiber negative electrode material for sodium ion battery in Comparative Example 1 of the present invention;

[0037] Figure 8 This is a performance ratio diagram of the reed carbon fiber negative electrode material for sodium ion battery in Examples 1 to 4 of the present invention and Comparative Example 1;

[0038] Fig. 9 This is the XRD diagram of the reed carbon fiber negative electrode material for sodium ion battery in Example 1 of the present invention;

[0039] Fig.10 This is a scanning electron microscope (SEM) image of the reed carbon fiber negative electrode material for sodium ion battery in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0043] Example 1

[0044] This embodiment provides a method for preparing a reed carbon fiber negative electrode material for a sodium ion battery. The specific preparation process is as follows: Figure 1 As shown, the following steps are included:

[0045] (1) Add 10 g of reed to 100 ml of 2% NaOH solution and stir at 80°C for 8 h. After the reaction is completed, cool to room temperature to obtain a dark brown suspension. Centrifuge and dry in a drying oven at 60°C for 12 h to obtain the desiliconized reed;

[0046] (2) Add the reed obtained in step (1) to a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N-dimethylformamide, and acetic acid, the masses of zinc nitrate and tetrafluoroterephthalic acid are 60.0 mg and 30.0 mg respectively; the volume of N,N-dimethylformamide and acetic acid is 7:1 (5 ml). Carry out solvent thermal reaction at 180°C for 12-24 hours. After the reaction is completed, cool to room temperature, take out, wash with ethanol several times, and dry in a 60°C vacuum drying oven for 12 hours to obtain a reed material with surface coated with uio66-4f;

[0047] (3) The uio66-4f obtained in step (2) is dried and placed in a tubular furnace connected to nitrogen for pyrolysis and carbonization, and the temperature is increased to 500°C at 5°C / min. After being kept warm for 1 hour, the temperature is continued to be increased to 900°C at 5°C / min and kept warm for 2 hours. After pyrolysis and carbonization, it is cooled to room temperature to obtain a reed carbon fiber negative electrode material for sodium ion batteries.

[0048] The scanning electron microscopy of the reed carbon fiber negative electrode material for sodium ion battery prepared in this example is as follows Figure 2 As shown in ae, the XRD pattern is Fig. 9 As shown, it can be seen that the microscopic morphology of the negative electrode material is fibrous, with a diameter in the range of 8 to 10 μm, an average diameter of about 8 μm, and a uniform size distribution; the XRD pattern of the reed carbon fiber negative electrode material for sodium ion battery prepared in this embodiment is as shown in Fig. 9 As shown, it can be seen that in addition to the (002) and (001) peaks of the carbon material, the strong peak appearing before 10° marks the synthesis of uio66-4f on the reed carbon material, and the surface of the reed carbon fiber carrier is coated with uio66-4f after zinc ion evaporation.

[0049] The application of the reed carbon fiber negative electrode material for sodium ion battery prepared in this embodiment comprises the following steps:

[0050] Take 0.15g of the reed carbon fiber negative electrode material powder for sodium ion battery prepared in this embodiment, mix it with conductive carbon black and a binder (PVDF), the mass ratio of the reed carbon fiber negative electrode material, the conductive carbon black and the binder is 8:1:1, add the resulting mixture into N-methylpyrrolidone solvent and stir for 6 hours, then coat it on copper foil to prepare a negative electrode sheet, and then use a metal sodium sheet as a counter electrode, a Diglyme mixture of NaPF6 as an electrolyte, and a Whatman GF / C glass fiber separator as a diaphragm to assemble into a button battery.

[0051] The electrochemical performance of the button battery was tested, and it was found that the reed carbon fiber negative electrode material for the sodium ion battery of this embodiment had an initial discharge capacity of 434.9 mAh / g, a charge capacity of 259.2 mAh / g, and an initial coulombic efficiency of 59.6% when the charge and discharge current was 200 mA / g. The initial charge and discharge curve is shown in FIG. Figure 3 As shown in the figure, it can be seen that the voltage hysteresis effect of the charging curve and the discharging curve is small, and the rate performance is as follows Figure 8 As shown, it can meet the requirements of sodium-ion batteries for high voltage and high energy density.

[0052] Example 2

[0053] This embodiment provides a method for preparing a reed carbon fiber negative electrode material for a sodium ion battery, comprising the following steps:

[0054] (1) Add 10 g of reed to 100 ml of 2% NaOH solution and stir at 80°C for 8 h. After the reaction is completed, cool to room temperature to obtain a dark brown suspension. Centrifuge and dry in a drying oven at 60°C for 12 h to obtain the desiliconized reed;

[0055] (2) Add the reed obtained in step (1) to a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N-dimethylformamide, and acetic acid, wherein the mass of zinc nitrate and tetrafluoroterephthalic acid is 60.0 mg and 20.0 mg respectively; the volume of N,N-dimethylformamide and acetic acid is 7:1 (5 ml). Carry out solvent thermal reaction at 180°C for 12-24 hours. After the reaction is completed, cool to room temperature, take out, wash with ethanol several times, and dry in a 60°C vacuum drying oven for 12 hours to obtain a reed material with surface coated with uio66-4f;

[0056] (3) The uio66-4f obtained in step (2) is dried and placed in a tubular furnace connected to nitrogen for pyrolysis and carbonization, and the temperature is increased to 500°C at 5°C / min. After being kept warm for 1 hour, the temperature is continued to be increased to 900°C at 5°C / min and kept warm for 2 hours. After pyrolysis and carbonization, it is cooled to room temperature to obtain a reed carbon fiber negative electrode material for sodium ion batteries.

[0057] The scanning electron microscopy of the reed carbon fiber negative electrode material for sodium ion battery prepared in this example is as follows Figure 2 As shown in bf, it can be seen that the microscopic morphology of the negative electrode material is fibrous, with a diameter in the range of 8 to 10 um, an average diameter of about 8 um, and a uniform size distribution. The surface of the reed carbon fiber carrier is coated with uio66-4f after zinc ion evaporation.

[0058] The button cell was assembled according to the application scheme in Example 1, and the electrochemical performance of the button cell was tested. It was found that the reed carbon fiber negative electrode material prepared in this example had an initial discharge capacity of 404.7 mAh / g, a charge capacity of 272.5 mAh / g, and an initial coulombic efficiency of 67.3% when the charge and discharge current was 200 mA / g. The initial charge and discharge curve is shown in FIG. Figure 4 As shown in the figure, it can be seen that the voltage hysteresis effect of the charging curve and the discharging curve is small, and the rate performance is as follows Figure 8 As shown, it can meet the requirements of sodium-ion batteries for high voltage and high energy density.

[0059] Example 3

[0060] A method for preparing the reed carbon fiber negative electrode material for a sodium ion battery prepared in this embodiment comprises the following steps:

[0061] (1) Add 10 g of reed to 100 ml of 2% NaOH solution and stir at 80°C for 8 h. After the reaction is completed, cool to room temperature to obtain a dark brown suspension. Centrifuge and dry in a drying oven at 60°C for 12 h to obtain the desiliconized reed;

[0062] (2) Add the reed obtained in step (1) to a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N-dimethylformamide, and acetic acid, wherein the mass of zinc nitrate and tetrafluoroterephthalic acid is 60.0 mg and 30.0 mg respectively; the volume of N,N-dimethylformamide and acetic acid is 5:1 (8 ml). Carry out solvent thermal reaction at 180°C for 12-24 hours. After the reaction is completed, cool to room temperature, take out, wash with ethanol several times, and dry in a 60°C vacuum drying oven for 12 hours to obtain a reed material with surface coated with uio66-4f;

[0063] (3) The uio66-4f obtained in step (2) is dried and placed in a tubular furnace connected to nitrogen for pyrolysis and carbonization, and the temperature is increased to 500°C at 5°C / min. After being kept warm for 1 hour, the temperature is continued to be increased to 900°C at 5°C / min and kept warm for 2 hours. After pyrolysis and carbonization, it is cooled to room temperature to obtain a reed carbon fiber negative electrode material for sodium ion batteries.

[0064] The scanning electron microscopy of the reed carbon fiber negative electrode material for sodium ion battery prepared in this example is as follows Figure 2 As shown in the CG, it can be seen that the microscopic morphology of the negative electrode material is fibrous, with a diameter in the range of 8 to 10 μm, an average diameter of about 8 μm, and a uniform size distribution. The surface of the reed carbon fiber carrier is coated with uio66-4f after zinc ion evaporation.

[0065] The button cell was assembled according to the application scheme in Example 1, and the electrochemical performance of the button cell was tested. It was found that the reed carbon fiber negative electrode material prepared in this example had an initial discharge capacity of 399.3 mAh / g, a charge capacity of 256 mAh / g, and an initial coulombic efficiency of 64.1% when the charge and discharge current was 200 mA / g. The initial charge and discharge curve is shown in FIG. Figure 5 As shown in the figure, it can be seen that the voltage hysteresis effect of the charging curve and the discharging curve is small, and the rate performance is as follows Figure 8 As shown, it can meet the requirements of sodium-ion batteries for high voltage and high energy density.

[0066] Example 4

[0067] A method for preparing the reed carbon fiber negative electrode material for a sodium ion battery prepared in this embodiment comprises the following steps:

[0068] (1) Add 10 g of reed to 100 ml of 2% NaOH solution and stir at 80°C for 8 h. After the reaction is completed, cool to room temperature to obtain a dark brown suspension. Centrifuge and dry in a drying oven at 60°C for 12 h to obtain the desiliconized reed;

[0069] (2) Add the reed obtained in step (1) to a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N-dimethylformamide, and acetic acid, wherein the masses of zinc nitrate and tetrafluoroterephthalic acid are 60.0 mg and 20.0 mg, respectively; the volume of N,N-dimethylformamide and acetic acid is 5:1 (8 ml). Carry out a solvent thermal reaction at 180°C for 12-24 hours. After the reaction is completed, cool to room temperature, take out, wash with ethanol several times, and dry in a 60°C vacuum drying oven for 12 hours to obtain a reed material with a surface coated with uio66-4f;

[0070] (3) The uio66-4f obtained in step (2) is dried and placed in a tubular furnace connected to nitrogen for pyrolysis and carbonization, and the temperature is increased to 500°C at 5°C / min. After being kept warm for 1 hour, the temperature is continued to be increased to 900°C at 5°C / min and kept warm for 2 hours. After pyrolysis and carbonization, it is cooled to room temperature to obtain a reed carbon fiber negative electrode material for sodium ion batteries.

[0071] The scanning electron microscopy of the reed carbon fiber negative electrode material for sodium ion battery prepared in this example is as follows Figure 2 As shown in DH, it can be seen that the microscopic morphology of the negative electrode material is fibrous, with a diameter of 8 to 10 μm, an average diameter of about 8 μm, and a uniform size distribution. The surface of the reed carbon fiber carrier is coated with uio66-4f after zinc ion evaporation.

[0072] The button cell was assembled according to the application scheme in Example 1, and the electrochemical performance of the button cell was tested. It was found that the reed carbon fiber negative electrode material prepared in this example had an initial discharge capacity of 380.7 mAh / g, a charge capacity of 241.9 mAh / g, and an initial coulombic efficiency of 63.5% when the charge and discharge current was 200 mA / g. The initial charge and discharge curve is shown in FIG. Figure 6 As shown in the figure, it can be seen that the voltage hysteresis effect of the charging curve and the discharging curve is small, and the rate performance is as follows Figure 8 As shown, it can meet the requirements of sodium-ion batteries for high voltage and high energy density.

[0073] Comparative Example 1

[0074] A method for preparing a reed carbon fiber negative electrode material for a sodium ion battery comprises the following steps:

[0075] Weigh 5g of reed and put it into a nitrogen-filled tubular furnace for pyrolysis and carbonization. Raise the temperature to 500℃ at 5℃ / min, keep it warm for 1h, and then continue to raise the temperature to 900℃ at 5℃ / min and keep it warm for 2h. After pyrolysis and carbonization, cool it to room temperature to obtain a powdered carbon material. The scanning electron microscope image of the carbon material in this comparative example is as follows: Fig.10 As shown, the spherical substance is the morphology of the Si element contained in the reed itself after aggregation, and it can be seen that the material is fibrous.

[0076] The button battery was assembled according to the application scheme in Example 1, and the electrochemical performance of the button battery was tested. It was found that the reed carbon fiber negative electrode material prepared in this example had an initial discharge capacity of 279.2 mAh / g, a charge capacity of 142.8 mAh / g, and an initial coulombic efficiency of 51.1% when the charge and discharge current was 200 mA / g. The initial charge and discharge curve was as follows: Figure 7 As shown, the specific capacity data of the reed carbon fiber negative electrode material obtained in other embodiments is lower than that in other embodiments.

[0077] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, and then modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a reed carbon fiber negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) Pre-treating reeds; (2) adding the reed obtained in step (1) into a mixed solution containing tetrafluoroterephthalic acid, zinc nitrate, N,N-dimethylformamide and acetic acid, performing a solvent thermal reaction, washing and drying, and obtaining a reed material with a surface coated with uio66-4f; (3) The reed material with surface coated with uio66-4f obtained in step (2) is carbonized at high temperature under a protective atmosphere to obtain a reed carbon fiber negative electrode material for a sodium ion battery.

2. The preparation method according to claim 1, characterized in that The pretreatment in step (1) comprises: soaking the reeds in a sodium hydroxide solution, stirring for 2 to 8 hours, washing with deionized water and drying.

3. The preparation method according to claim 1, characterized in that: The reaction temperature of the solvent thermal reaction in step (2) is 120-220° C., and the reaction time is 8 to 48 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of tetrafluoroterephthalic acid to zinc nitrate is 1:2-2:3, and the volume ratio of N,N-dimethylformamide to acetic acid is 5:

7.

5. The preparation method according to claim 1, characterized in that: The cleaning in step (2) uses ethanol, and the drying temperature is 40-80° C. and the drying time is 6-18 hours.

6. The preparation method according to claim 1, characterized in that: The protective atmosphere in step (3) is a nitrogen or argon atmosphere, and the high-temperature carbonization adopts a two-stage sintering. The first stage is sintered at a heating rate of 2 to 5°C / min to 350-600°C and kept warm for 1 to 2 hours; the second stage is sintered at a heating rate of 2 to 5°C / min to 800-1000°C and kept warm for 1 to 2 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The reed is fibrous, has a fiber diameter of 8-10 μm, and is produced in the Dongting Lake area.

8. A reed carbon fiber negative electrode material for sodium ion battery, characterized in that: The negative electrode material is prepared by the preparation method of reed carbon fiber negative electrode material for sodium ion battery as described in any one of claims 1-6, and the negative electrode material uses reed carbon fiber as a carrier, and the surface of the reed carbon fiber is coated with UIO66-4F.

9. A reed carbon fiber negative electrode material for sodium ion battery, characterized in that: The reed carbon fiber negative electrode material is used in sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method for nitrogen-phosphorus co-doped flexible carbon fiber membrane used as negative electrode material

    CN106099055A

  • Plant fiber three-dimensional structural carbon material used as cathode material of sodium-ion battery and lithium ion battery and preparation method thereof

    CN106654267A

  • Method for preparing hollow porous Na2MnPO4F / C nanometer fiber positive electrode material

    CN107039641A

  • N and S self-doped reed-based hard carbon sodium battery negative electrode material and preparation method thereof

    CN116169266A